(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A review of current problems in otorhinolaryngology is made, in particular cysts of the nasal adnexa, which develop among the most complex non-purulent processes. Cysts are mainly incidental abnormalities in the diagnosis of paranasal diseases. The work presents modern data on the etiology, pathogenesis, health characteristics, methods of diagnosis and treatment of cysts of paranasal diseases using the latest scientific achievements. The developed minimally invasive methods of surgical treatment, these principles, reduce the risk of developing postoperative complications and shorten the treatment time for patients. However, despite this, the question of the advantages and principles of various methods for removing cysts of accessory teeth, which have not yet been replaced by traditional solutions, remains controversial.